The gastrodin biosynthetic pathway in Pholidota chinensis Lindl. revealed by transcriptome and metabolome profiling - Liu, Baocai; Chen, Jingying; Zhang, Wujun; Huang, Yingzhen; Zhao, Yunqing; Juneidi, Seifu; Dekebo, Aman; Wang, Meijuan; Shi, Le; Hu, Xuebo (Frontiers in Plant Science, 2022)
Pholidota chinensis Lindl. is an epiphytic or a lithophytic perennial herb of Orchidaceae famly used as a garden flower or medicinal plant to treat high blood pressure, dizziness and headache in traditional Chinese medicine (TCM). The gastrodin (GAS) is considered as a main bioactive c constituent reported in P. chinensis. However, GAS biosynthetic pathway in P. chinensis remains unclear. To elucidate the GAS biosynthesis and to identify the related genes in P. chinensis, a comprehensive analysis of transcriptome and metabolome of roots, rhizomes, pseudobulbs and leaves were performed by using PacBio SMART, Illumina Hiseq and Ultra Performance Liquid Chromatography Tandem Mass Spectrometry (UPLC-MS/MS). A total of 1156 metabolites were identified by UPLC-MS/MS, of which 345 differential metabolites were mainly enriched in phenylpropanoid/ phenylalanine, flavone and flavonol biosynthesis. The pseudobulbs make up almost half of the fresh weight of the whole plant, but the GAS content was also the highest in four tissues. The Unigenes (23105), with an average length of 2186 bp, were obtained functionally and 22029 transcripts were annotated. The 7787, 8376 and 9146 differentially expressed genes (DEGs) were identified in rhizomes, pseudobulbs and leaves respectively in comparison with the roots, and 16175 DEGs were identified in the four targeted tissues. A total of 80 Unigenes were identified as encoding eight key enzymes that control GAS biosynthesis namely: phenylalanine ammonia-lyase (PAL), trans-cinnamate 4-monooxygenase (CYP73A), 4-coumarate: CoA ligase (4CL), shikimate O-hydroxycinnamoyltransferase (HCT), 5-O-(4-coumaroyl)-D-quinate 3'-monooxygenase(C3H), Caffeoyl coenzyme A-O-methyltransferase (CCoAOMT), alcohol dehydrogenases (ADH) and Glucosyltransferase (GT). In the last step, the key enzyme GT had 39 Unigenes. Through the analysis of expression, phylogenetic tree, and homologous searching, the transcript28360/f2p0/1592 in GT3 was putatively identified as a candidate gene. For further validation, the expression levels of Unigenes were measured using a quantitative real-time PCR. The metabolomics and transcriptomics of B3 vs B1 group integrated analysis showed that 8,376 DEGs and 345 DEMs had a substantial association based on the Pearson’s correlation. This finding notably enriched the metabolomic and transcriptomic data of P. chinensis, and it provides valuable information for the identification of candidate genes involved in the biosynthesis of GAS.